Consumer Preference Level on Cinnamomum burmanii Tea with Analytic Hierarchy Process Method - Yulia Citra; Susi Susi; Hisyam Musthafa Al Hakim (TROPICAL WETLAND JOURNAL, 2018)
Cinnamon is one of the popular ingredients used as food additives or nonfood. Cinnamon has smells fragrant and sweet taste, it can be used as additional ingredient for tea bag production. Tea with additional cinnamon is one of product innovation of tea bag for increase functional value of tea. The purpose of this research is to know consumer preferences level of cinnamon tea based on internal attribute (colour, taste, and scent) and external attribute (packaging design, packaging material, information label, size and content of packaging) using Analytic Hierarchy Process (AHP) method. The result of consumer preferences of cinnamon tea based on Analitic Hierarchy Process (AHP) method as primary alternative for internal attribute based on color, taste, and smell is 2:1 formulation of ratio tea powder and cinnamon powder. The primary alternative of external attribute based on design, material, information label, size of packaging is prototype C (carton packaging).